EUROASPIRE IV: A European Society of Cardiology survey on the lifestyle, risk factor and therapeutic management of coronary patients from 24 European countries - Kotseva, Kornelia; Wood, David; De Bacquer, Dirk; De Backer, Guy; Rydén, Lars; Jennings, Catriona; Gyberg, Viveca; Amouyel, Philippe; Bruthans, Jan; Castro Conde, Almudena; Cífková, Renata; Deckers, Jaap W; et al. (European journal of preventive cardiology, 2016)
AIMS: To determine whether the Joint European Societies guidelines on cardiovascular prevention are being followed in everyday clinical practice of secondary prevention and to describe the lifestyle, risk factor and therapeutic management of coronary patients across Europe. METHODS AND RESULTS: EUROASPIRE IV was a cross-sectional study undertaken at 78 centres from 24 European countries. Patients <80 years with coronary disease who had coronary artery bypass graft, percutaneous coronary intervention or an acute coronary syndrome were identified from hospital records and interviewed and examined ≥ 6 months later. A total of 16,426 medical records were reviewed and 7998 patients (24.4% females) interviewed. At interview, 16.0% of patients smoked cigarettes, and 48.6% of those smoking at the time of the event were persistent smokers. Little or no physical activity was reported by 59.9%; 37.6% were obese (BMI ≥ 30 kg/m(2)) and 58.2% centrally obese (waist circumference ≥ 102 cm in men or ≥88 cm in women); 42.7% had blood pressure ≥ 140/90 mmHg (≥140/80 in people with diabetes); 80.5% had low-density lipoprotein cholesterol ≥ 1.8 mmol/l and 26.8% reported having diabetes. Cardioprotective medication was: anti-platelets 93.8%; beta-blockers 82.6%; angiotensin-converting enzyme inhibitors/angiotensin receptor blockers 75.1%; and statins 85.7%. Of the patients 50.7% were advised to participate in a cardiac rehabilitation programme and 81.3% of those advised attended at least one-half of the sessions. CONCLUSION: A large majority of coronary patients do not achieve the guideline standards for secondary prevention with high prevalences of persistent smoking, unhealthy diets, physical inactivity and consequently most patients are overweight or obese with a high prevalence of diabetes. Risk factor control is inadequate despite high reported use of medications and there are large variations in secondary prevention practice between centres. Less than one-half of the coronary patients access cardiac prevention and rehabilitation programmes. All coronary and vascular patients require a modern preventive cardiology programme, appropriately adapted to medical and cultural settings in each country, to achieve healthier lifestyles, better risk factor control and adherence with cardioprotective medications.
Keywords: dospělí; lékařská praxe - způsoby provádění; Guideline Adherence; Smoking; Sedentary Behavior; hodnocení rizik; chování snižující riziko; Female; Europe; Prevalence; Adult; Smoking Cessation; výsledek terapie; ženské pohlaví; průzkumy zdravotní péče; průřezové studie; sedavý životní styl; mladý dospělý; Adolescent; kardiovaskulární látky; kouření; koronární nemoc; časové faktory; Time Factors; komorbidita; lidé; Coronary Disease; Evropa; cvičení; Comorbidity; odvykání kouření; Treatment Outcome; Risk Assessment; společnosti lékařské; Societies, Medical; dieta; Risk Factors; prevalence; Risk Reduction Behavior; prospektivní studie; sekundární prevence; směrnice pro lékařskou praxi jako téma; Cross-Sectional Studies; Diet; Aged; Cardiovascular Agents; Male; Practice Guidelines as Topic; Prospective Studies; Secondary Prevention; kardiologie; Young Adult; Cardiology; rizikové faktory; lidé středního věku; senioři; mužské pohlaví; Exercise; Health Care Surveys; Middle Aged; mladiství; dodržování směrnic; Practice Patterns, Physicians'; Humans